1076 The impact of shiftwork on sleep quality among nhs nurses. (24th April 2018) - McDowall, K; Murphy, E; Anderson, K
Abstract : Introduction: Shiftwork is common amongst nurses and it is known to be a workplace hazard as it may cause poor sleep quality, which can impact adversely on the health and safety of nurses and their patients. The aims of this study were to identify and describe the association between poor sleep quality and shiftwork in nurses. Additionally, to explore factors that contribute to poor sleep quality and to assess the awareness of support from Occupational Health (OH). Methods: Cross-sectional study of nurses at a National Health Service Foundation Trust, February to March 2016. Data was collected via an online questionnaire. Sleep quality was measured using the Pittsburgh Sleep Quality Index. Result: 888 nurses participated; 34% response rate. The prevalence of poor sleep quality was 78% (95% CI: 0.748 to 0.813) in the shift working nurses (SWNs), compared to 59% (95% CI: 0.503 to 0.678) in the non-shift working nurses (NSWNs). There was a mean sleep quality score difference of 1.58 between the SWNs and the NSWNs, which was statistically significant, p<0.001 (95% CI: 0.913 to 2.246). Undertaking shiftwork was the only significant association with poor sleep quality, when controlling for the other variables of age, gender and number of years worked, OR 0.410 p <0.001 (95% CI: 0.265 to 0.634). Discussion: There is a higher prevalence of poor sleep quality in SWNs compared to NSWNs. OH should be aware of any form of shiftwork as an important risk factor for poor sleep, as well as Trust managers acknowledging this workplace hazard. OH can provide staff with support for good sleep practice which aims to lead to healthier nurses.